Pengembangan Kompetensi Arsiparis di IAIN Kerinci: Meningkatkan Efisiensi dan Transparansi Pengelolaan Arsip Perguruan Tinggi - Marlina, Andi; Ikhsan, Rizal; Ravico, Ravico; Desviana Siregar, Anggi; Seprina Anggraini, Reri (Fakultas Ushuluddin, Adab, dan Dakwah, 2025)
Efficient and transparent archival management is a crucial aspect in supporting the smooth operation of higher education institutions, including IAIN Kerinci. Although there are regulations governing archival management, such as those outlined in Law No. 43 of 2009 on Archiving, archival management at IAIN Kerinci still faces various challenges, particularly related to the limited human resources (HR) with expertise in archiving and the suboptimal management of digital archives. This study aims to evaluate the existing archival management system at IAIN Kerinci, identify the challenges faced, and provide solutions through functional archivist training. The method used is a qualitative approach, conducting Functional Archivist Education and Training (Diklat) focused on improving technical competencies in managing both manual and digital archives. The results show that this training successfully enhanced archivists' skills in managing archives in a more organized, efficient, and technology-aligned manner. The implications of this study emphasize the importance of increasing HR capacity in archival management and the application of technology in digital archival systems to improve transparency and accountability. In conclusion, this training program significantly contributes to more efficient archival management at IAIN Kerinci, which in turn supports administrative processes and decision-making based on accurate and secure data.